Răspuns :
[tex]2) - \frac{1}{3} - \frac{5}{4} \div ( - \frac{15}{16} )[/tex]
[tex] = - \frac{1}{3} - \frac{5}{4} \times ( - \frac{16}{15} )[/tex]
[tex] = - \frac{1}{3} + \frac{4}{3} = \frac{ - 1 + 4}{3} = \frac{3}{3} = 1[/tex]
[tex]3)3 \sqrt{225} + 12 \sqrt{121} - \sqrt{169} [/tex]
[tex] = 3 \times 15 + 12 \times 11 - 13[/tex]
[tex] = 45 + 132 - 13[/tex]
[tex] = 177 - 13[/tex]
[tex] = 164[/tex]
[tex] = - \frac{1}{3} - \frac{5}{4} \times ( - \frac{16}{15} )[/tex]
[tex] = - \frac{1}{3} + \frac{4}{3} = \frac{ - 1 + 4}{3} = \frac{3}{3} = 1[/tex]
[tex]3)3 \sqrt{225} + 12 \sqrt{121} - \sqrt{169} [/tex]
[tex] = 3 \times 15 + 12 \times 11 - 13[/tex]
[tex] = 45 + 132 - 13[/tex]
[tex] = 177 - 13[/tex]
[tex] = 164[/tex]
[tex]2) - \frac{1}{3} - \frac{5}{4} : ( - \frac{15}{16}) = \\ \\ \frac{5}{4} : ( - \frac{15}{16}) = \frac{5}{4} \times \frac{ - 16}{15} = \frac{5 \times ( - 16)}{4 \times 15} = - \frac{80}{60}^{(20} = - \frac{4}{3} \\ \\ - \frac{1}{3} - ( - \frac{4}{3}) = \frac{ - 1 - ( - 4)}{3} = \frac{3}{3} = 1 [/tex]
[tex]3)3 \sqrt{225} + 12 \sqrt{121} - \sqrt{169} = \\ \\ 3 \times 15 + 12 \times 11 - 13 = \\ \\ 45 + 132 - 13 = \\ \\ 177 - 13 = \\ \\ 164 [/tex]
[tex]3)3 \sqrt{225} + 12 \sqrt{121} - \sqrt{169} = \\ \\ 3 \times 15 + 12 \times 11 - 13 = \\ \\ 45 + 132 - 13 = \\ \\ 177 - 13 = \\ \\ 164 [/tex]